PENGARUH PENDIDIKAN KESEHATAN TENTANG SADARI TERHADAP PENGETAHUAN DAN PERILAKU DETEKSI DINI KANKER PAYUDARA PADA REMAJA PUTRI DI MAN MODEL BANDA ACEH - Nurhayati Nurhayati; Nilawati Nilawati; Alvira Alvira (Journal Keperawatan, 2023)
The incidence of breast cancer is increasing every year. One of the effective efforts to prevent breast cancer early is through SADARI (Breast Self-Examination). This study aims to determine the effect of health education about awareness on the behavior of early detection of breast cancer in young women at MAN Model Banda Aceh. The research design used is Quasi-Experimental with cluster sampling technique. The samples taken in this study were 16 year old girls at MAN Model Banda Aceh. The research was conducted from 12 October 2021 to 22 April 2022. The Wilcoxon statistical test results on knowledge both before and after receiving health education with a p value = 0.001 (p <0.05), while for abilities both before and after being given health education it was found that the p value = 0.004 because the p value <0.05 so it can be concluded that there is an influence of health education about breast self-examination (BSE) on the knowledge and behavior of female students in efforts to detect early breast cancer in the MAN Model Banda Aceh.